Response to the Vegetative Growth of Arabica Coffee Plants (Coffea Arabika) Due to Seed Depth Test and Application of Eco Enzyme - Yudi Siswanto; Isnar Sumartono; Muhammad Wasito; Nurloza Khatimah (CV Raskha Media Group, 2025)
The purpose of this study was to determine the vegetative growth response of Arabica coffee (Coffea arabica) resulting from different seed planting depths and eco-enzyme application, as well as their interaction effects. The research was conducted in Sei Sikambing B Village, Medan Sunggal District, Medan City, North Sumatra Province, at an altitude of approximately ±25 meters above sea level. The study took place from July to October 2025. This research used a Factorial Randomized Block Design (RBD). The first factor was seed depth, denoted as